Dermatology life quality index in psoriasis patients attending a tertiary care hospital: a study from North India - Shah, Faizan Younus; Kitab, Ifrah Shafat; Shah, Aaqib Aslam; Shah, Faisal Younis; Shah, Mohd Younus; Ain, Qurat ul; Renzu, Mahvish (International Journal of Research in Medical Sciences, 2020)
Background: Psoriasis affects nearly 1% of the world population. It can be a source of significant morbidity and psychological stress to the patient but is not lethal under ordinary circumstances. Patients suffering from the disease feel a lack of empathy on part of care-givers, family members, healthcare professionals as well as society in general. Dermatology life quality index (DLQI) is a questionnaire-based assessment of health related quality of life in patients suffering from skin disorders and has been seen to correlate well with the impact of the disease on a patient. This study was done to understand the impact of psoriasis on the overall well-being of patients using DLQI as the tool of assessment. Methods: The study included 40 cases of psoriasis that were assessed for the severity of the disease based on percentage body surface area involvement. The impact of disease severity and other factors on the quality of life of the patient was assessed using DLQI. Results: Out of 35 patients with BSA involvement <50% (mild and moderate disease), 28.6% (n=10/35) showed a very large or extremely large effect on the quality of life while no patient with a BSA involvement >50% (severe and very severe disease) reported the same. A small, moderate or no effect on the DLQI was seen in 71.4% (n=25/35) of cases from the mild and moderate disease group while 100% (n=5/5) of cases from severe and very severe disease group reported a similar effect. Thus, DLQI was not directly related to the extent of BSA involvement and was dependent on other factors as well. Conclusion: Age had a correlation with the effect of the disease on the quality of life of psoriasis cases. Patients who were younger were more likely to report stress and anxiety related to the recurrences seen with the disease. Patients with lesions on sites that are socially exposed like face, hands, scalp, etc. were more likely to feel embarrassed about their condition. Younger age, female gender, lesions on exposed sites and recently diagnosed patients (<12 months) were factors which had a significant impact on the health-related quality of life of patients. The severity of disease and extent of involvement were not always directly related to extent of impact on the quality of life.